Designs for Learning Environments of the Future International Perspectives from the Learning Sciences - Jacobson, Michael J.; Reimann, Peter; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Few things are as certain as societal changes$1 (Band the pressing need for educators to prepare students with the knowledge and ways of thinking necessary for the challenges in a changing world. In the forward-thinking pages of Designs for Learning Environments of the Future, international teams of researchers present emerging developments and findings in learning sciences and technologies at the infrastructure, curricular, and classroom levels. Focusing on ideas about designing innovative environments for learning in areas such as biology, engineering, genetics, mathematics, and computer science, the book surveys a range of learning technologies being explored around the world$1 (Ba spectrum as diverse as digital media, computer modeling, and 3D virtual worlds$1 (Band addresses challenges arising from their design and use. The editors$1 (Bholistic perspective frames these innovations as not only discrete technologies but as flexible learning environments that foster student engagement, participation, and collaboration. Contributors describe possibilities for teaching and learning in these and other cutting-edge areas: Working with hypermodels and model-based reasoning Using visual representations in teaching abstract concepts Designing strategies for learning in virtual worlds Supporting net-based collaborative teams Integrating innovative learning technologies into schools Developing personal learning communities Designs for Learning Environments of the Future will enhance the work of a wide range of professionals, including researchers and graduate students in the learning and cognitive sciences, and educators in the physical and social sciences.s
Invention and Innovation in Designing Future Learning Environments -- MaterialSim: A Constructionist Agent-Based Modeling Approach to Engineering Education -- Learning Genetics from Dragons: From Computer-Based Manipulatives to Hypermodels -- The Development of River City, a Multi-User Virtual Environment-Based Scientific Inquiry Curriculum: Historical and Design Evolutions -- Design Perspectives for Learning in Virtual Worlds -- Learning to Learn and Work in Net-Based Teams: Supporting Emergent Collaboration with Visualization Tools -- Learning Mathematics Through Inquiry: A Large-Scale Evaluation -- Scaffolding Knowledge Communities in the Classroom: New Opportunities in the Web 2.0 Era -- From New Technological Infrastructures to Curricular Activity Systems: Advanced Designs for Teaching and Learning -- Toward a Theory of Personalized Learning Communities -- Afterword: Opportunities for Transformational Learning.
Keywords: Education; Education; Educational Technology; Computers and Education; Learning & Instruction